Numerical Simulation and Experimental Study of Fuzzy-PID Control Method for Liquid Nitrogen Direct Evaporation Refrigeration System - Hong Xing; Wu Jingyi; Wang Shanshan (Zhileng xuebao)
More presetting tasks for parameters in traditional PID controlling are required, thereby leading to complex processes, unsatisfied control effects, and poor adoption for system condition changing. In the liquid nitrogen direct evaporation refrigeration system, a fuzzy-PID control strategy was proposed based on the dynamic distributing parameter model of the systemto meet the requirements of the high-precision temperature controlling. Simulations were performed to analyze the effect of the control strategy in combination with the proposed model, indicating the sound adoption of the control strategy on the system. Experiments for the application of the control strategy were designed to investigate the control effect under the condition of target temperature ?50 ℃, ?80 ℃, or ?140 ℃. Experiment results showed that the maximum relative deviation of the simulation results on the experiment results reached 7.8%, and that the temperature fluctuations under different conditions are ±0.5 ℃, 1.0 ℃, or 2.0 ℃, which increased as the target temperature decreased.